EFFICIENCY OF LOW DOSE 30MCI OF I-131 FOR LOW TO INTERMEDIATE RISK THYROID CANCERS USING TRIPLE NEGATIVE CRITERIA - Jamali, Asifa; Ram, Nanik; Khalid, Farah; Kazi, Mabrooka; Islam, Najmul (Journal of Ayub Medical College Abbottabad, 2025)
Background: Radioiodine-131 ablation (RAI) of residual functioning thyroid tissue is a staple in the treatment of many Thyroid Cancer patients after surgery. However, it is debated and reexamined to avoid overtreatment of low-risk carcinomas and improve the detection of tumors that are more aggressive. We determined the difference in treatment response during one year after ablation. Moreover, we investigated differences between patients who did not undergo RAI Treatments and compared them to patients receiving a low dose of iodine (30 mCi). Methods: This was a retrospective study conducted at Aga Khan University Hospital (AKUH) in Karachi, Pakistan. The study population was patients with low to intermediate risk of well Differentiated thyroid cancers (DTC). A descriptive analysis was done. Categorical variables were represented as frequencies and percentages. The comparison was done by Chi-square. Results: Out of 102 participants, mean age was 41.88 years and the majority were females (73.5%). The common diagnosis was papillary thyroid carcinoma (84.3%). A low recurrence risk was reported in 89.2%. 98% of patients were given a 30-mci dose of RAI. The majority 83.3% of participants reported a Post-ablative Whole-body iodine scan (WBIS) showing no distant metastasis 1 year after RAI ablation. 55.8% of participants reported an excellent response to treatment, followed by 17.65% of participants having incomplete biochemical responses. Conclusion: This study concludes that a low dose of RAI provided an excellent response to treatment in contrast to patients who had no RAI dose. After 1 year of follow-up, ultrasound imaging showed negative structural recurrence in the majority of patients which proves that a low dose of RAI can help for a disease-free follow-up.